Performance Evaluation of Fully Automated Reticulocyte Count As A Validated Method In Comparison with Manual Count In Neonates - Swati, Usman Tahir; Mahmood, Asad; Zahir, Saima; Bozdar, Manzar; Ali, Sadia; Ahmed, Tanweer (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the performance of fully automated reticulocyte count as a validated method in comparison with manual count in neonates. Study Design: cross-sectional study. Place and Duration of Study: Department of Haematology, Armed Forces Institute of Pathology (AFIP), from July 2020 to December 2020. Methodology: 103 healthy neonates of either gender were selected using non-probability convenience sampling. Venous blood of the participants was collected and reticulocyte count was determined using both manual count as well as Sysmex XN-3000 Automated Haematology Analyzer. The data was recorded, tabulated and processed to ascertain the degree of correlation and agreement between the two methods using Linear Regression Analysis and Bland-Altman plot respectively. Results: The mean age of participants was 14 days. Out of the total of 103 participants, gender-wise distribution was 55(53%) males and 48(47%) females. The mean manual reticulocyte count was 2.0+1.1% and automated reticulocyte count was 2.0+ 1.0%. The two sets of data showed good correlation with a coefficient of correlation (r) of 0.97. The mean bias of data was 0.002 with good agreement as all recorded data points fell between upper and lower limits of agreement. Conclusion: Our findings suggest that automated haematology analyzers can offer a high-throughput method of determining reticulocyte count with an adequately close agreement of results to the well-established manual method.